Abstracts Communications Orales - Radiopédiatrie_ JRANF 2025_JAIM 2025_17.3 - SAKHO Aminata,; SANSUAMOU TEC,; SOMÉ MILCKISEDEK JUDICAËL MAROURUANA,; DONGMO SYLVIANE,; MOIFO Boniface,; GUI-BILE LYNDA NADINE,; Yannick ONANA,; LUCIENNE IRENE PATRICIA ONDIMA,; ELION OSSIBI PIERLESKY,; ABDEL-SAMAD ADJANAYO, (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2025)
4-Abstracts Communications Orales - Radiopédiatrie_ JRANF 2025_JAIM 2025_17.3